A novel near-infrared probe for the imaging of superoxide anion fluctuations and hydrogen ion enhancement in vivo. Issue 30 (18th July 2018) - Sun, Chunlong; Du, Wen; Zhang, Wei; Wu, Yang; Yao, Zhigang; Wang, Baoqin; Wu, Tao; Yang, Hongjun; Wang, YanMei; Ren, Lili
Abstract : A novel synthesized reaction-based near-infrared imaging probe (IR-747-SAPH) exhibits high selectivity to O2 ˙ − and H + fluxes in vivo . Abstract : Superoxide anions (O2 ˙ − ) and hydrogen ions (H + ) have attracted considerable attention in studies on cellular dysfunction. A newly synthesized reaction-based near-infrared imaging probe (IR-747-SAPH), which is composed of a superoxide anion responsive group and a H + responsive group, exhibits high selectivity to O2 ˙ − and H + fluxes in vivo . The fluorescence intensity of IR-747-SAPH changes as O2 ˙ − and H + concentrations vary. IR-747-SAPH is characterized by sensitivity to changes in H +, high photostability, and strong near-infrared properties, including high temporal resolution, deep penetration, and low background interference. The probe also provides reliable near-infrared fluorescence signals that alter O2 ˙ − and H + levels in vivo . Therefore, IR-747-SAPH fluorescence imaging is a promising detection method for monitoring the changes in O2 ˙ − and H + in various biological environments.